17.8k views
2 votes
Drag each expression to show whether it is equivalent to −2.6x−(−5.9x), −2.6x+(−5.9x), or neither. −2.6x−5.9x 5.9x+(−2.6x) 5.9x−(−2.6x) −5.9x+(−2.6x) −2.6x+5.9x −5.9x+2.6x −2.6x−(−5.9x) −2.6x+(−5.9x) Neither

User Liesbeth
by
5.1k points

1 Answer

6 votes

Answer:

The 2 expressions are:

1) −2.6x−(−5.9x) = −2.6x + 5.9x

2) −2.6x+(−5.9x) = −2.6x - 5.9x

Options:

−2.6x−5.9x -> equivalent to 2nd expression

5.9x+(−2.6x) = −2.6x) + 5.9x -> equivalent to 1st expression

5.9x−(−2.6x) = 5.9x + 2.6x = 2.6x + 5.9x -> equivalent to neither expression

−5.9x+(−2.6x) = −5.9x − 2.6x = − 2.6x − 5.9x -> equivalent to 2nd expression

−2.6x+5.9x -> equivalent to 1st expression

−5.9x+2.6x = 2.6x − 5.9x -> equivalent to neither expression

User Scarlet
by
5.1k points